Modernisasi Pendidikan Islam: Pengalaman Lembaga Pendidikan Al-Ittihadiyah - Dedi Sahputra Napitupulu (Journal of Education and Teaching Learning, 2021)
Al-Ittihadiyah is one of the largest and oldest Islamic organizations in Indonesia. Born on January 27, 1935 ago, Al-Ittihadiyah played an important role in the movement of Muslims, both in education, social, da'wah, and politics. Using a qualitatively descriptive approach as well as referring to primary literartur, this paper aims to determine the modernization of Islamic education at AL-Ittihadiyah educational institutions which include objectives, curriculum and education methods Al-Ittihadiyah. In addition, this paper also explains how the role of Al-Ittihadiyah in social, political, economic and religious fields. The results showed that the education institution presence of Al-Ittihadiyah is very influential in the community, it is shown from the many educational institutions Al-Ittihadiyah ranging from public schools, Madrasah, to the college Scattered throughout the archipelago that has produced many alumni and each of them has been instrumental in the midst of society